Resveratrol improves cardiovascular function and reduces oxidative organ damage in the renal, cardiovascular and cerebral tissues of two-kidney, one-clip hypertensive rats - YARAT, AYŞEN; YEGEN, BERRAK; ALTURFAN, EBRU IŞIK (WILEY, 2010)
Objectives The putative protective effects of resveratrol against oxidative injury in the heart, kidney and brain tissues of rats induced with the two-kidney, one-clip (2K1C) hypertension model were investigated. Methods Wistar albino rats were divided into sham-operated (n = 8) or 2K1C groups, in which rats received either resveratrol (10 mg/kg per day, i.p., n = 8), or saline (n = 8) starting at Week 3 after the surgery and continuing for the following 6 weeks. Indirect blood pressure recordings and echocardiographic images were made to evaluate cardiac function. At the end of Week 9 the animals were decapitated and plasma, heart, kidney and brain were taken for biochemical assays, while aortic rings were prepared for vascular reactivity studies. Key findings 2K1C hypertension resulted in increased blood pressure, aortic hypercontractility and reduced left ventricular function, leading to increased lipid peroxidation and myeloperoxidase activity, concomitant with significant reductions in tissue glutathione, superoxide dismutase, Na+/K+-ATPase and catalase activities in the cardiac, renal and brain tissues, indicating the presence of oxidative tissue damage in peripheral target organs. Elevated plasma levels of lactate dehydrogenase, creatine kinase, as well as reduced plasma levels of antioxidant capacity and nitric oxide further verified the severity of oxidative injury. A 6-week treatment with resveratrol reversed all the measured parameters, ameliorated hypertension-induced oxidative injury in the target organs and improved cardiovascular function. Conclusions Resveratrol improved cardiovascular function through the augmentation of endogenous antioxidants and the inhibition of lipid peroxidation by maintaining a balance in oxidant/antioxidant status, which also ameliorated hypertension-induced oxidative injury in the cardiac, renal and cerebral tissues.
Keywords: hypertension; Na+/K+-ATPase; oxidative stress; resveratrol; WINE POLYPHENOL RESVERATROL; RENIN-ANGIOTENSIN SYSTEM; RED WINE; SUPEROXIDE-DISMUTASE; LIPID-PEROXIDATION; ENDOTHELIAL DYSFUNCTION; INDUCED CARDIOTOXICITY; VASCULAR DYSFUNCTION; NADPH OXIDASE; CAUSAL ROLE